Admin911: SMS - Trent Rod (American : MC Graw Hill, 2000)
"Call on Admin911 to learn what’s going on with your network, to understand your options, and pick the right solutions." -David Chernicoff, Windows 2000 Magazine This essential survival guide for system administrators contains problem-solving and troubleshooting techniques for Microsoft System Management Server. Kathy Ivens is Series Editor.
Keywords: Server Installation; Admin911; Netwrk Optimization